Kajian Bahasa Pendidik di Kabupaten Mimika: Educational Language Study in Mimika District - Siswanto Siswanto; Normawati Normawati (Balai Bahasa Provinsi Papua, 2020)
One of the skills to be mastered well by teachers to show their professional identity as an academic community is writing skills. This research aims at describing effective sentences and ineffective sentences produced by junior high school teachers in Mimika Regency, Papua Province and describe the causes of ineffectiveness based on theoretical framework. The results of this study are expected to be useful to develop the ability of teachers to deal with problems in classroom learning, especially problems relating to writing sentences in scientific work. In addition, this study serves as a material consideration in an effort to improve the quality of teachers and schools so as to improve the quality and achievements of graduates. This study uses a descriptive method to describe the latest conditions related to the ability of non-language teachers in junior high schools to write scientific papers in the form of writing class action research reports. Exposure is focused on the ability, language knowledge, and experience of writing non-language teachers in developing the ability to write classroom action research. Based on an analysis of eleven manuscripts, the number of effective sentences is less than the ineffective sentences. This shows that generally writers have not been able to make good texts. The main cause of the ineffectiveness of the sentences produced by the teacher is due to the influence of spoken language.